Evaluative criteria applied by selected female fashion consumers in the Vaal Region when purchasing casual daywear - Hugo, Susanna Hendrina (My University, 2007)
Criteria used by fashion consumers to assess the quality of apparel products during the decision-making process are a good indication of what considerations to keep in mind for customer satisfaction. Evaluative criteria of concern to apparel customers are intrinsic attributes, involving physical features such as design/style, materials and construction and performance features such as aesthetic and functional aspects and extrinsic attributes such as price, brand, store image, label, country of origin and appropriateness for the occasion, in this case casual day wear. The broad research aim of this exploratory study was to determine which evaluative criteria were used by female fashion consumers in the Vaal Region to determine apparel quality when purchasing casual daywear, and to what extent the various criteria were applied. A self-administered, structured questionnaire was used to collect the data. Sections 1 and 2 measured the importance of intrinsic and extrinsic clothing evaluative criteria. Section 3 investigated the frequency with which the respondents bought casual daywear at various store types, namely specialty, department and discount stores, while section 4 gathered the demographic information of the respondents. A representative sample was chosen from the academic personnel of all seven tertiary institutions in the Vaal Region. The majority of the lecturers (38.00 percent) were between the ages of 31 and 40, which can be described as relatively young, constituting a group sometimes referred to as baby busters or Generation X. Although the predominant population group was white (65.71 percent), a quarter of the respondents were black. They all had a tertiary qualification, indicating a relatively high educational level, and an average income. These espondents were predominantly married, either by orthodox or customary marriage. Regarding the application of evaluative criteria for quality assessment, these respondents used intrinsic apparel attributes to a greater extent than extrinsic attributes. Three functional performance aspects namely durability, comfort and fit were rated equal and most important for judging quality, followed closely by an extrinsic attribute namely appropriateness for casual daywear. Three clusters of respondents could be distinguished, each with a specific disposition towards the evaluative criteria. The most popular store type for clothing was Department stores, followed by Discount and Specialty stores.
M. Tech. (Fashion, Department of Arts and Design, Faculty of Human Sciences): Vaal University of Technology
Keywords: Fashion consumers; Day wear; 646.4; Clothing trade -- South Africa.; Fashion merchandising -- South Africa.